L’image de l’oasis comme matériel de terrain - Irène Carpentier (EchoGéo)
Oasis iconography is rich and longstanding, but its use in research remains little explained. Returning to our thesis fields, in Tozeur and Gabes in Tunisia, this article questions the role of photography in the construction of the oasian territorial imaginary, and of research on these places. As an original field material, the photo in the oases constitutes a resource for various discourses on the territory, between the promotion of a touristic dream, a description of a landscape, or the raising of awareness about environmental degradation. In a first part, we will see the reappropriation of the abundant colonial corpus in the frame of an idealization of ancient systems. Then we will assess the process of constituting a “witness corpus” to environmental degradation in a context of associative dynamism. Finally, we will expore the way in which research can mobilize this field material to better understand the diversity of development dynamics in oasian’ territories.